Late recognition of Gore Helex atrial septal occluder fracture and migration. Issue 3 (September 2021) - Tyagi, Sudhi; Patil, Harshal; Cinquegrani, Michael; Pearson, Paul; Joyce, Lyle; Garster, Noelle; Salinger, Michael
Abstract: Patent foramen ovale (PFO) closure is indicated in cryptogenic stroke. Percutaneous PFO closure is both feasible and highly efficacious with low incidence of device-related complications. When complications occur, they are usually discovered within 6 weeks of device deployment. We describe the case of a partially embolised and fractured Gore Helex Septal Occluder device recognised nearly 9 years after placement requiring surgical explant. <Learning objective: Device-related complications with patent foramen ovale closure devices are exceeding rare. Our case highlights the need for continued long-term device monitoring with periodic imaging given the ongoing risk for device-related complications.>